Aplicación de la contabilidad comercial en “Servirepuestos Salazar” del cantón Latacunga, provincia de Cotopaxi período mayo- junio 2016 - Jácome Vásquez, Luis Patricio (2017)
The present research work entitled "COMMERCIAL ACCOUNTING IN" SERVIREPUESTOS SALAZAR "OF CANTÓN LATACUNGA, PROVINCE OF COTOPAXI PERIOD MAY-JUNE 2016, is oriented to the structuring of an accounting tool necessary to keep the accounting and economic records produced in the same. In order to meet the objectives set forth and provide its owner with a fundamental contribution of how to carry out a detailed control and proper management of its economic resources, carrying out the implementation of the accounting process by the permanent inventory system, so that it allows you to know The real situation of your business; And as a prerequisite to elect the degree of Accounting and Auditing Engineer, CPA. It was necessary to carry out the initial inventory based on the physical verification of the source documentation, the memorandum of operations was drawn up, a plan and accounts manual according to the business need to perform the accounting records and comply with the accounting process, additional Records and auxiliary accounting were designed. Finally, when implementing the commercial accounting from the physical verification to the presentation of the financial statements I can conclude that through the development of the accounting process I can determine the usefulness of the exercise for USD $ 3.787,31 so I recommend the lady owner To accept the proposed accounting design, and thus may have relevant and reliable financial statements for timely decision making.